AGE RELATED CHANGES IN HISTOMORPHOLOGY OF MEDIUM SIZED MUSCULAR ARTERY: Histomorphology of Muscular Artery - Khan, Muhammad Marghoob; Butt, Shadab Ahmed; Kiani, Muhammad Rizwan Bashir (Pakistan Armed Forces Medical Journal, 2014)
Objective: The aim of this study was to contribute to the knowledge of histomorphometric changes which are associated with increasing age in local population, with the experience obtained in the dissection on cadavers. Study Design: Cross-sectional comparative study Place and Duration of Study: The study was carried out at the department of Anatomy, Army Medical College Rawalpindi in collaboration with Forensic departments of various medical institutes where cadavers were brought for autopsy, spanning from 15 Feb 2010 to 15 Aug 2010. Material and Methods: A total of forty cadavers from local population (Punjab and Khyber Pakhtunkhwa) were dissected and specimen (Common hepatic artery) (CHA) were obtained. Two age groups, one below the age of forty years (1 to 39 years) and the other above the age of forty years (40 to 70 years) were made. The specimen were processed and stained with Hematoxylin and Eosin. Using a microscope with 10 X objective, micrometry was done and data of intima thickness (IT), media thickness (MT) and intima media thickness (IMT) was noted. Results: After comparing the two age groups, statistically significant difference was found between the IT (p value <0.01). The mean values of media failed to attain any statistical difference. No statistically significant difference was found in the IMT of the two age groups. Conclusion: Increase in itima thickness was found while MT and IMT did not show any statistical difference.